A Systematic Review to Advance Cost Management Strategies for Rail Projects (International Journal of Built Environment and Sustainability, 2024)
Developing a robust rail network has always been a priority for countries, especially those in the process of development. The growth of the rail industry plays a crucial role in boosting a nation's economy and productivity. As multiple national governments are actively developing rail projects to transform public transport from road to rail, it is evident that the knowledge in rail construction cost management needs a revamp after 20 years of research, hence the need of this study. The purpose of this paper is to provide an in-depth review aimed at establishing a standardized framework for identifying and categorizing the factors affecting cost performance in rail projects. As part of this study, a Systematic Literature Review (SLR) of journal publications on rail project cost management from 2016 to 2023 has been started to ascertain the noteworthy contributions that various stakeholders and educators contributed to the knowledge of cost management in rail projects. Ultimately, 23 publications had been selected to be critically analyzed. The analysis sheds light on current research trends, highlights gaps in existing knowledge, and suggests potential avenues for future research. The significant research findings include the need to explore effective stakeholder management in rail projects, developing effective mechanism/framework for all parties to ensure effective cost management and enhancing the connection between research and industry practice in the rail industry. Furthermore, as the thorough examination of literature identifies the research trends, researchers may delve into the fundamental concepts of the subject, draw valuable insights from the assessments, and progress towards areas where research is most needed as well as providing stakeholders and academics with impactful outcome for enhancing rail project cost management in the future.
Keywords: Construction Project Management, Cost Management, Rail Infrastructure